Vulnerability Assessment of Climate Change in Vietnam: A Case Study of Binh Chanh District, Ho Chi Minh City - Truong, Dinh Duc; Dat, Tran Tho; Hang, Nguyen Dieu; Huan, Le Huy (Frontiers in Environmental Science, 2022)
Climate change poses additional obstacles to poverty eradication and social justice. Rising temperatures, abnormal rainfall increases, storms, floods, and droughts have become more frequent and severe phenomena in Vietnam. This causes serious consequences for the livelihood security of the poor. Binh Chanh district (Ho Chi Minh City) is an area subject to severe risks of climate change in the Mekong River Delta, Vietnam. Here, the low-income groups are the most vulnerable because their adaptive capacity is still limited and low. This study uses the livelihood vulnerability index (LVI) to assess the level of vulnerability to climate change in households and communes in the Binh Chanh district. LVI includes three components: exposure (E), sensitivity (S), and adaptive capacity (AC) based on 23 indicators selected by reviewing the literature and consulting with experts. The article also conducted surveys with 931 households in 16 administrative communes in Binh Chanh for primary data. The research results showed that Tan Kien and An Phu Tay communes have the highest level of vulnerability since they are areas with mainly low-lying terrain and contiguous location rivers; the people in these towns are also vulnerable groups because they do not have a stable source of income, skills, and have low education and experience in climate change adaptation. The study also proposes some solutions to improve the capacity to adapt to climate change of vulnerable communes specifically: 1) creating diversified livelihoods with stable incomes; 2) deploying community-based climate change adaptation models for communes adjacent to rivers; 3) implementing adaptive agriculture and improving social capital for vulnerable households; 4) building resettlement areas for households heavily affected by disasters; and 5) raising awareness among low-income households to respond to natural hazards in the context of climate change.